1995
DOI: 10.1111/j.1525-1594.1995.tb02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of Hemolysis in a Centrifugal Ventricular Assist Device

Abstract: This paper describes the use of computational fluid dynamics (CFD) to predict numerically the hemolysis in centrifugal pumps. A numerical hydrodynamical model, based on the full Navier-Stokes equation, was used to obtain the flow in a vaneless centrifugal pump (of corotating disks type). After proper postprocessing, critical zones in the channel were identified by means of two-dimensional color-coded maps of %Hb release. Simulation of different conditions revealed that flow behavior at the entrance region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Miyazoe et al (1998Miyazoe et al ( , 1999, concluded that CFD could be a useful tool for developing blood pumps, but no direct comparisons between hemolysis tests and visualization tests were actually performed. Work reported by Pinotti and Rosa (1995), Nishida et al (1999) and Takiura et al (1998), focused on centrifugal pumps. Takiura et al (1998) compared a selection of their CFD results with hemolysis tests and concluded that they were consistent.…”
Section: Discussionmentioning
confidence: 98%
“…Miyazoe et al (1998Miyazoe et al ( , 1999, concluded that CFD could be a useful tool for developing blood pumps, but no direct comparisons between hemolysis tests and visualization tests were actually performed. Work reported by Pinotti and Rosa (1995), Nishida et al (1999) and Takiura et al (1998), focused on centrifugal pumps. Takiura et al (1998) compared a selection of their CFD results with hemolysis tests and concluded that they were consistent.…”
Section: Discussionmentioning
confidence: 98%
“…The threshold for platelet activation according to the Hellums' criterion is represented by a shear stressexposure time product of 35 dyne·s/cm 2 . Although some of the aforementioned models satisfy certain experimental observations, they have also been shown to mostly underestimate cell damage (33,34). Under physiological flow conditions and blood flow through devices, blood is exposed to varying stress levels resulting in blood damage that differs from the ideal case of constant stress (30,34).The magnitude of stress accumulation that leads to cell (RBC/platelet) damage is not clear.…”
mentioning
confidence: 97%
“…Based on these observations, mathematical correlations to estimate the percent hemoglobin release were developed (30,31). A similar model was also developed for platelet activation based on percent release of dehydrogenase (lactate dehydrogenase) from platelets (30).The relation between stress and exposure time that results in hemolysis and in platelet activation has been well established for the case of constant stress.…”
mentioning
confidence: 99%
“…After the damage D n of each erythrocyte is analyzed for each streamline from the inlet to the outlet of the pump, the average damage D passing through the pump is regarded as the estimated hemolysis. Many studies have examined the effect of shear stress and the exposure time for the hemolysis in the blood pump (Pinotti and Rosa 1995), whereas other Table 13.7 Coefficients for hemolysis and shear stress (Blackshear et al 1965;Heuser 1980;Wurzinger et al 1985;Giersiepen et al 1990;Song et al 2004 785 Range of τ and t -4 0 < τ < 700 57 < τ < 255 0.0034 < t < 0.6 0.007 < t < 0.7 studies have examined additionally the effect of the pressure (Mizuguchi et al 1995). Some earlier studies have analyzed the shear stress (Wood et al 1999), and some studies have analyzed the relationship between the experimental results and hemolysis test results (Miyazoe et al 1998).…”
Section: Cfd Of Hemolysismentioning
confidence: 99%